Ocular manifestations of liver disease in children: Clinical aspects and implications - Durga Prasad; Arpita Bhriguvanshi (Annals of Hepatology, 2020)
Liver and eyes are interlinked to each other in various medical conditions. There are certain ocular findings which directly indicate specific liver disorders. Thus, it becomes critical to identify disorders of liver and eyes early in the course of illness, so that prompt management may be initiated before the commencement of complications. It is highly advantageous in metabolic liver disorders as it offers prognostic value and spares the patient of unnecessary invasive and detailed work up. However, due to its silent and heterogeneous presentation, it is often unrecognized and ignored. Eye abnormalities could be due to, either direct toxic effects of abnormal metabolites, excess of normal metabolites, or by deficient energy metabolism. A number of inherited liver conditions have associated ocular lesions such as Kayser–Fleischer rings in Wilson's disease, posterior embryotoxon or optic drusen in Alagille's syndrome, and cherry-red spot in Niemann–Pick's type A. A thorough eye examination is important in distinguishing between several different forms of familial intrahepatic cholestasis which are associated with anomalies of the heart, bones, or kidneys. Early diagnosis is important, as in most cases, dietary restriction and early therapy prevents the onset of disability. The aim of this review is to sensitize and make pediatricians, hepatologists and ophthalmologists aware of specific ocular findings, suggestive of certain hepatobiliary disorders, thus helping in early referral. The pediatric and adult literature was thoroughly reviewed to organize the present review.